The Road to Serfdom after 75 Years - Caldwell, Bruce (Journal of Economic Literature, 2020)
This paper revisits Friedrich Hayek’s book, The Road to Serfdom, on the seventy-fifth anniversary of its publication. Though the book is well-known, its arguments are often mischaracterized. The paper traces the origins of the book, noting the various people and arguments that Hayek was responding to, and places it in the context of its times. The structure of the book is explored and some common criticisms addressed. Finally, it is shown how, after its publication, the book took on a life of its own. (JEL B25, B31, P11, P16, P21, P26)